Bach2 repression mediates Th17 cell induced inflammation and associates with clinical features of advanced disease in chronic pancreatitis. Issue 2 (1st March 2018) - Sasikala, M; Ravikanth, VV; Murali Manohar, K; Deshpande, Neha; Singh, Sandhya; Pavan Kumar, P; Talukdar, R; Ghosh, Sudip; Aslam, Mohsin; Rao, GV; Pradeep, R; Reddy, D Nageshwar
Abstract : Objectives: Altered immune homeostasis and involvement of T cells has been reported in chronic pancreatitis (CP). We evaluated the role of Bach2 (BTB and CNC homology basic leucine zipper transcription factor 2), a key regulator of immune homeostasis in the chronicity of CP. Methods: Expression of Bach2 and T‐cell transcription factors, enumeration of BACH2+/CD4+ T‐lymphocytes were performed by qRT‐PCR and flow cytometry respectively. Bach2 silenced human CD4+ T‐lymphocytes were exposed to CP tissue extract to assess T‐cell lineage commitment. Aryl hydrocarbon receptor ( Ahr ) and Deubiquitinase enzyme A (DUBA/ OTUD5gene ) were evaluated as markers of persistent Th17 cell differentiation. Bach2 gene (exons) was sequenced to identify risk variants and functionally validated. Results: Decrease in Bach2 ( p < 0 . 0001) and increase ( p < 0 . 001) in TBX21, RORC, Ahr, PRDM1, IL23R mRNA were noted in pancreatic tissues, while BACH2+/CD4+ T‐lymphocytes were decreased ( p < 0.01) in circulation and tissues. Exposure of Bach2 silenced CD4+ T‐lymphocytes to CP tissue extract showed increased Ahr, decreased OTUD5, and enhanced Th17 cell differentiation. Sequencing of Bach2 gene revealed association of novel variant (rs9111 in 5′‐UTR) with advanced disease and luciferase assay confirmed its role in Bach2 repression. Conclusion: Bach2 repression mediates Th17 cell induced inflammation and rs9111‐TT in individuals with primary genetic susceptibility to CP is associated with clinical features of advanced disease.